Tingkat Kepuasan Pengunjung Terhadap Objek Wisata Pulau Kumala di Kutai Kartanegara - Ema Dwi Arsita; Novi Sunu Sri Giriwati (RUAS, 2022)
East Borneo has a lot of potential and natural resources that have not been fully developed, including in the tourism sector. Kutai Kartanegara Regency is experienced rapid progress in the tourism sector and continues to be developed until now. One of the popular tourist objects is Kumala Island as a cultural tourism object. However, within one year this tourist attraction experienced a decrease in the number of visitors because the management was considered less than optimal. Therefore, there is a need for a study of the level of visitor satisfaction at a tourist attraction to see what facilities must be improved in order to attract visitors again. This study uses a descriptive qualitative method with a Likert scale to see the level of satisfaction of visitors to Kumala Island tourism. From the research results, the Attractions and Accessibility aspects in Kulau Kumala have been satisfactory, but the amenities are still unsatisfactory so they must be addressed to attract visitors again.